Historicizing renewables: issues and challenges. (2nd October 2021) - Hasenöhrl, Ute; Kupper, Patrick
ABSTRACT: The essay discusses some main challenges involved in historicizing renewables. It highlights three approaches that we regard as central for re- and deconstructing the history of renewables, and which show potential for rethinking familiar narratives in both the history of technology and environmental history. First, we argue that the adoption or rejection of renewables was specific to place and time and thus can only be understood within a framework of sociotechnological change. Second, we stress that the term renewables has its own history and that the term and its equivalents not only represented a number of technologies and energy carriers but also signified certain ideas about present and future society. Third, we explain why a deeper knowledge of how renewable energies were utilized throughout history not only leads to a better understanding of the past, but might help to identify challenges and pitfalls in current energy transitions.